PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII E SMP NEGERI 13 PALU PADA MATERI PERSAMAAN GARIS LURUS: Application of The Problem Based Learning (PBL) Model to Improve Student Learning Outcomes in Class VIII E SMP Negeri 13 Palu on Straight Line Equations - ISNANIYAH, LAILA; Alfisyahra; Nurhayadi (Universitas Tadulako, 2023)
This study aims to describe the application of learning modelsProblem Based Learning (PBL) the can improve the learning outcomes of class VIII E students of SMP Negeri 13 Palu on the material of straight line equations. This type of research is Classroom Action Research (PTK) and its design uses the Kemmis and Mc. Taggart, namely planning, action, observation, and reflection. The subjects of this research were all students of class VIII E SMP Negeri 13 Palu with a total of 30 students and three students were selected as informants. The results showed that through the application of learning modelsProblem Based Learning (PBL) can improve student learning outcomes by following the model phasesProblem Based Learning as follows: (1) students' orientation to problems, (2) organizing students to learn, (3) assisting individual and group investigations, (4) developing and presenting work, and (5) analyzing and evaluating the problem-solving process. Based on the data on learning outcomes in cycle I, it can be seen that the mastery of classical learning reached 30% and in cycle II it was 76.6%. Furthermore, the results of observations in cycle I on teacher activity obtained a score of 30, which was included in the good category and the results of observations of student activities obtained a score of 26, which was included in the less category based on the intervals previously made. Then the results of observations in cycle II on teacher activity obtained a score of 38 which was included in the very good category and the results of student activities obtained a score of 35 which was included in the good category based on the intervals previously made.